Analysis of mechanical behavior of termoplastic composites - Kuzu, Ali Taner; Kösemen, Elifnur; Yücel, Aysu Hande; Bakkal, Mustafa (Necip Fazıl YILMAZ, 2021)
This paper presents the effect of fiber orientation on the tensile, compression, impact, and flexuralproperties of glass fiber reinforced acrylic-based thermoplastic composites. The mechanical behaviorof three different composite plates, produced by the resin transfer molding (RTM) method, with0°/90°/45°, 0°/90° and ±45° glass fiber orientations were investigated by carrying out tensile,compression, three-point bending and Charpy impact tests. A Weibull distribution model wasimplemented to explain the variation in mechanical properties of the acrylic-based composite.According to Weibull analysis results with 63.2% probability, the highest tensile strength (561 MPa),compressive strength (293 MPa) and impact values (19.44 J) were obtained when the plate with0°/90° glass fiber orientation was tested, whereas the highest flexural strength was obtained when theplate with 0°/90°/45° was tested. Publisher's Version
Keywords: Composite and Hybrid Materials; Thermoplastic matrix; Kompozit ve Hibrit Malzemeler; Mechanical Engineering; Mechanical testing; composites; mechanical testing; thermoplastic matrix; Makine Mühendisliği; Composites